Hierarchical Modeling of Patient and Physician Determinants of Blood Pressure Outcomes in Adherent vs Nonadherent Hypertensive Patients: Pooled Analysis of 6 Studies With 14, 646 Evaluable Patients. Issue 9 (12th July 2013) - Abraham, Ivo; Van Camp, Yoleen; Villa, Lorenzo; Denhaerynck, Kris; Sun, Diana; Vancayzeele, Stefaan; Brié, Heidi; Aerts, Ann; Hermans, Christine; MacDonald, Karen
Abstract : The authors used pooled data from 6 valsartan‐related studies including 3983 adherent and 10, 663 nonadherent patients to evaluate blood pressure (BP) outcomes in both groups after 90 days of treatment, applying hierarchical linear and logistic regression to identify determinants of BP outcomes. The principal findings were that: (1) BP outcomes were consistently better in adherent patients; (2) approximately a quarter of the variance in 90‐day BP values was attributable to a physician class effect; (3) common and unique patient‐ and physician‐related variables were associated with BP outcomes in both groups; (4) physician vigilance was associated with better outcomes, especially in adherent patients; and (5) adherent patients were more likely to exhibit target organ damage and associated events while being prescribed more complex medication regimens. Adherence to antihypertensive medication may be a function of prior line treatment failure, severity of illness, and sequelae, and the ensuing patient resolution to change medication behavior.